GENDER STEREOTYPES AND THEIR IMPACT ON THE FAMILIES OF WOMEN LEADERS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
In modern societies, the number of women in leadership positions has been steadily increasing; however, gender stereotypes continue to exert a significant influence on both professional and private spheres of women leaders’ lives. This article examines the concept of gender stereotypes and analyzes their impact on the family lives of women leaders. Using a qualitative and analytical approach, the study explores how traditional gender norms affect role distribution within families, work–family balance, psychological well-being, and social perceptions. The findings suggest that persistent gender stereotypes place a “double burden” on women leaders, negatively influencing family dynamics and emotional health. At the same time, the article highlights emerging positive trends related to shared responsibilities and changing societal attitudes. The study emphasizes the importance of promoting gender equality to ensure sustainable leadership and family well-being.